(untitled) (Annals of Medical Research, 2021)
Aim: Candidemia is a life-threatening infection that has been reported to be associated with poorer outcomes in trauma patients. The present study aimed to investigate the epidemiology of candidemia in non-burn patients with polytrauma.Material and Methods: We conducted a retrospective, single-center, observational study of polytrauma patients with candidemia admitted to the surgical intensive care units of a university hospital in Turkey between 2013 and 2017 on. Results: The incidence of candidemia was 127 episodes per 1000 intensive care unit admissions in polytrauma patients. Non-albicans Candida species accounted for 75.5% of all candidemia episodes. C. parapsilosis (51.05%) was the predominant species, followed by C. albicans (24.52%) and C. tropicalis (12.21%). The highest crude mortality rate (72%) was observed in patients with C. parapsilosis candidemia. In multivariate analyses, who had undergone prior gastrointestinal surgery were 7.1 times more likely to have C. parapsilosis candidemia than those with other strains.Conclusion: Our study, remarkable, demonstrated a high incidence of Candidemia had in polytrauma patients, and non-albicans Candida species were the most frequently isolated candida species. According to our study findings, a prior history of gastrointestinal surgery may help predict C. parapsilosis, as the causative agent of candidemia in polytrauma patients. However, since our study was observational and limited to such a small number of patients, the results obtained should be applied with caution.